Kapudánságok a bosnyák határvidéken a 16-18. században - Moačanin, Nenad (Array, 1999)
Having compared data concerning captaincies in Ottoman Bosnia the author concludes that the chief or grat captains connected with river or maritime navigation and warfare had been replaced by smaller captains at the beginning of the 17th c. who acted also as commanders of small fortresses with no waterways in the vicinity. They came from among Vlachs and local Muslim militia, eventually succeeding in making their posts a kind of a hereditary fief.